The Effect of Expressive Writing Therapy in Reducing Anxiety Levels in Adolescent Bullying Victims - Syah, Afni Yan (Babali Publisher, 2023)
Introduction: Bullying is a social phenomenon that often occurs in society, especially in adolescents. There are many biological, psychological, and social changes that can cause conflict problems between themselves and the surrounding environment, causing bullying victims which have an impact on the emergence of anxiety in these adolescents. The purpose of this study was to determine the effectiveness of expressive writing therapy in reducing the level of anxiety among adolescent victims of bullying. Method: The research method used quasi-experimental research with pretest and posttest control group design approaches. The sampling technique with a total sampling of 44 respondents divided into 2, namely the experimental group and the control group. Results: the results of the study using the Paired Sample T-test showed that the value of p = 0.000 (p <0.05) which means that there is an effect of expressive writing therapy in reducing anxiety levels in adolescent victims of bullying. This can be seen from the decrease in anxiety scores in adolescent victims of bullying from a severe anxiety level of 50.0% to 41.0% in mild anxiety after expressive writing therapy intervention. Conclusion: Therefore, it is suggested that expressive writing therapy can be used as an intervention in overcoming anxiety in adolescent victims of bullying both on campus and at home.